Testing of available heavy metal content of soils in Long-Term Fertilization Trials with ryegrass (Lolium perenne L.) - Kiss, Zsanett; Lehoczky, Éva; Németh, Tamás (Acta Biologica Szegediensis, 2002)
A greenhouse pot experiment was set up to study the Cd and Cr uptake of ryegrass (Lolium perenne L.) from the National Long-Term Fertilization Trials (NLFT) in Keszthely. The soil used was Eutric cambisol. Soils samples were taken in October 2000 in the 34th years of the experiment. Ryegrass was grown for four weeks and the plants were cut above the soil. Fresh and dry biomass weight and Cd and Cr concentrations were measured. The "total" (cc. HN03 + cc. H2 02 soluble) Cd and Cr contents of the NLFT soils were determined. The "total" Cd content of the experimental soils ranged between 0.18-0.21 mg kg1 soil. The Cd concentration in the aboveground ryegrass parts was 0.14-0.27 mg kg-1 dry matter. The Cd content of plants was 76-141% of the soils' Cd content. It was found that the "total" Cr content of soils was 37.9-40.3 mg kg-1 soil. The Cr content of ryegrass was 2.68-6.09% of the soils' Cr content. The concentration of the examined toxic heavy metal in soils was only a fraction of the valid Hungarian maximum permissible quantity. No connection was found between fertilization and the amounts of elements.